2010
DOI: 10.1016/j.avsg.2009.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Combined Distal Venous Arterialization and Free Flap for Patients with Extensive Tissue Loss

Abstract: Aim:We evaluated the mid-term outcome of distal venous arterialization (DVA), and the role of a combined free flap as a bridgehead for blood supply. Methods:In the past 6 years, 9 patients with extensive tissue loss and lucking graftable distal arteries underwent DVA. These consisted of 4 primary DVAs, 3 combined DVA and free flap procedures, and 2 adjuvant DVAs for hemodynamically failed distal bypasses.After 9 primary DVAs, 3 redo DVAs were performed for early failure. Etiologies were 4Buerger's disease and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…The peripheral tissues are fi nally lost because of the oxygen defi cit. Patients with AO often suffer severe pain, and may be treated by distal venous arterialization (DVA) in an attempt to save the distal parts of the lower limbs from amputation [ 1 ]. This procedure involves diverting an intact (non-affected) artery (posterior tibial artery or dorsalis pedis artery) and connecting it to the plantar vein below the ankle after the valves in the vein have been carefully disrupted and rendered incompetent.…”
Section: Introductionmentioning
confidence: 99%
“…The peripheral tissues are fi nally lost because of the oxygen defi cit. Patients with AO often suffer severe pain, and may be treated by distal venous arterialization (DVA) in an attempt to save the distal parts of the lower limbs from amputation [ 1 ]. This procedure involves diverting an intact (non-affected) artery (posterior tibial artery or dorsalis pedis artery) and connecting it to the plantar vein below the ankle after the valves in the vein have been carefully disrupted and rendered incompetent.…”
Section: Introductionmentioning
confidence: 99%
“…The Duplex ultrasound (DUS) study was the most frequently reported follow-up method followed by TCPo 2 and angiography. 6,[8][9][10][11][12][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] Other methods infrequently used included ankle-brachial index (ABI), toebrachial index (TBI), toe pressure (TP), computed tomography (CT) angiography, and scintillography. 10,23 Duplex Ultrasound Some authors obtained DUS as early as 7 days postoperatively while one obtained the first DUS at week 6.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to noninvasive studies, four authors routinely performed digital subtraction angiography to evaluate venous arterializations. 18,19,22,23 Angiography can assess retrograde perfusion of the dorsal and deep plantar venous arches. 19 Additionally, angiography allows for interventions if the need is identified.…”
Section: Angiographymentioning
confidence: 99%
See 1 more Smart Citation
“…Distal venous arterialization may be offered as a last surgical resort for limb salvage in the absence of graftable distal arteries [185][186][187][188][189]. Distal venous arterialization can successfully salvage the critically ischaemic lower limb with few serious complications.…”
Section: Distal Revascularizationmentioning
confidence: 99%